2020
DOI: 10.1101/2020.11.29.401984
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Emetine as an antiviral agent suppresses SARS-CoV-2 replication by inhibitinginteraction of viral mRNAwith eIF4E: Anin vitrostudy

Abstract: Emetine is a FDA-approved drug for the treatment of amebiasis. In the recent times we had also demonstrated the antiviral efficacy of emetine against some RNA and DNA viruses. Following emergence of the COVID-19, we further evaluated thein vitro antiviral activity of emetine against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The therapeutic index of emetine was determined to be 10910.4, at a cytotoxic concentration 50 (CC50) of 1603.8 nM and effective concentration 50 (EC50) of 0.147 nM.Besi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…eir report was in line with that of Choy et al in showing in vitro anti-SARS-CoV-2 activities of emetine and homoharringtonine, at 2.55 and 0.46 μM, respectively [11,55]. Additionally, Kumar et al showed that emetine (2.3 ng/egg) inhibited SARS-CoV-2 replication via suppressing viral proteins such as viral polymerase in the infecting chicken embryonic model with IBV (chicken coronavirus) [56]. Also, another study showed that homoharringtonine strongly interacted with SARS-CoV-2 S protein among eleven anti-SARS-CoV alkaloids with a LibDock score of 109.11 kcal/mol [57].…”
Section: Alkaloids As Potential Phytochemicals Against Sars-cov-2supporting
confidence: 82%
“…eir report was in line with that of Choy et al in showing in vitro anti-SARS-CoV-2 activities of emetine and homoharringtonine, at 2.55 and 0.46 μM, respectively [11,55]. Additionally, Kumar et al showed that emetine (2.3 ng/egg) inhibited SARS-CoV-2 replication via suppressing viral proteins such as viral polymerase in the infecting chicken embryonic model with IBV (chicken coronavirus) [56]. Also, another study showed that homoharringtonine strongly interacted with SARS-CoV-2 S protein among eleven anti-SARS-CoV alkaloids with a LibDock score of 109.11 kcal/mol [57].…”
Section: Alkaloids As Potential Phytochemicals Against Sars-cov-2supporting
confidence: 82%
“…Were found to inhibit SARS-CoV helicase (nsp13) via inhibition of ATPase activity being a potential phytochemical inhibitor [73,74]. Emetine could be re-purposed to treat COVID-19 based on the in-vitro antiviral activity against SARS-CoV-2 and its ability to shield chicken embryos from IBV [75].…”
Section: Replicase Inhibitorsmentioning
confidence: 99%
“…Treatment with Emetine could decrease the replication of virus by decreasing the synthesis of RNA and protein. Emetine could disrupt the binding of the eukaryotic translation initiation factor (a cap-binding protein needed for translation) with SARS-CoV-2 RNA in an investigation using chromatin immunoprecipitation assay [73] , [76] .…”
Section: Drugs Repositioned To Target Sars-cov-2-s Protein and Rdrpmentioning
confidence: 99%